An Efficient Architecture and High-Throughput Implementation of CCSDS-123.0-B-2 Hybrid Entropy Coder Targeting Space-Grade SRAM FPGA Technology - Chatziantoniou, Panagiotis; Tsigkanos, Antonis; Theodoropoulos, Dimitris; Kranitis, Nektarios; Paschalis, Antonis (IEEE transactions on aerospace and electronic systems, 2022)
Nowadays, hyperspectral imaging is recognized as cornerstone remote sensing technology. The explosive growth in image data volume and instrument data rates, compete with limited on-board storage and downlink bandwidth, making hyperspectral data compression a mission critical task. Recently, the consultative committee for space data systems (CCSDS) extended the previous issue of the CCSDS-123.0 Recommended Standard for multi/hyperspectral image compression to provide Near-Lossless compression functionality. A key feature of the CCSDS-123.0-B-2 is the improved Hybrid Entropy Coder providing substantially better compression performance than the Issue 1 entropy coders at low bit rates. In this paper, we introduce a high-throughput hardware implementation of the CCSDS-123.0-B-2 Hybrid Entropy Coder. The introduced architecture exploits the systolic design pattern providing modularity and latency insensitivity in a deep and elastic pipeline, achieving constant throughput of 1 sample/cycle with small field programmable gate array (FPGA) resource footprint. This architecture is described in portable VHDL register-transfer level (RTL) and implemented, validated and demonstrated on a commercially available Xilinx KCU105 development board hosting a Xilinx Kintex Ultrascale XCKU040 SRAM FPGA, and thus, is directly transferable to the Xilinx Radiation Tolerant Kintex UltraScale XQRKU060 space-grade devices. Moreover, state-of-the-art SpaceFibre (ECSS-E-ST-50-11C) serial link interface and test equipment were used in the validation platform to emulate an on-board deployment. The introduced CCSDS-123.0-B-2 Hybrid Entropy Coder achieves a constant throughput performance of 305 MSamples/s. To the best of our knowledge, this is the first published fully-compliant architecture and high-throughput implementation of the CCSDS-123.0-B-2 Hybrid Entropy Coder, targeting space-grade FPGA technology.